2022
DOI: 10.1126/sciadv.abm6840
|View full text |Cite
|
Sign up to set email alerts
|

Umpolung carbonyls enable direct allylation and olefination of carbohydrates

Abstract: Mother Nature has its own arts to build a vast number of carbohydrates; however, there is still a lack of tools for selective functionalization of native carbohydrates through C─C bond formation. Such a long-standing challenge for the synthetic community lies into the intrinsic problems related to the innate properties of carbohydrates, e.g., the ease to oligomerization or polymerization, the difficulty of chemoselectivity control in the presence of multiple hydroxyl groups, the great challenge to retain the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“… 12 16 For example, the modern lexicon of coordination chemistry now contains X-, L-, or Z-type ligands, which indirectly describes the polarity of a metal–ligand bond by identifying the donor and acceptor involved in the interaction. 17 19 Reversal of expected bond polarity, or umpolung , is also an important concept with impacts in organic synthesis, 20 27 catalysis, 6 , 28 32 frustrated Lewis pairs, 33 , 34 and bonding in main group chemistry. 35 37 Another area in which bond polarity plays an important but underappreciated role is in coordination compounds containing heterometallic metal–metal bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 16 For example, the modern lexicon of coordination chemistry now contains X-, L-, or Z-type ligands, which indirectly describes the polarity of a metal–ligand bond by identifying the donor and acceptor involved in the interaction. 17 19 Reversal of expected bond polarity, or umpolung , is also an important concept with impacts in organic synthesis, 20 27 catalysis, 6 , 28 32 frustrated Lewis pairs, 33 , 34 and bonding in main group chemistry. 35 37 Another area in which bond polarity plays an important but underappreciated role is in coordination compounds containing heterometallic metal–metal bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Bond polarity is a fundamental property of chemical systems, with donor–acceptor interactions at the heart of acid–base reactions, organic chemistry, , inorganic solid state chemistry, and coordination chemistry. For example, the modern lexicon of coordination chemistry now contains X-, L-, or Z-type ligands, which indirectly describes the polarity of a metal–ligand bond by identifying the donor and acceptor involved in the interaction. Reversal of expected bond polarity, or umpolung , is also an important concept with impacts in organic synthesis, catalysis, , frustrated Lewis pairs, , and bonding in main group chemistry. Another area in which bond polarity plays an important but underappreciated role is in coordination compounds containing heterometallic metal–metal bonds. The recent explosion of interest in heterometallic compounds has produced a number of systematic series that illustrate how polarity impacts heterometallic bonding generally.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, inspired by the Wolff–Kishner reduction in which a carbanion was generated through hydrazone, metal catalyzed “umpolung” chemistry of hydrazones as alkyl carbanion equivalents has attracted much attention in organic synthesis and been widely applied in various addition and cross coupling reactions to construct C–C/O/N bonds. 5 As organometallic surrogates, the umpolung nucleophilic additions of non-substituted hydrazones with imines 5 b , e and other electrophiles exhibit green and sustainable characteristics with no waste metal salts or halides and with only nitrogen as the sole byproduct (Scheme 1B). 6,7 Moreover, hydrazones derived from aldehydes and ketones are easily available and moisture/air-stable.…”
mentioning
confidence: 99%
“…In our search for such a strategy, we realized that hydrazones, readily available from ketones, can react both as electrophiles and nucleophiles, 28 , 29 and can be used to functionalize unprotected carbohydrates. 30 Baldwin et al. demonstrated that lithiated trityl hydrazones act as 1,2-diazaallyl anions and add to aldehydes.…”
mentioning
confidence: 99%
“…In our search for such a strategy, we realized that hydrazones, readily available from ketones, can react both as electrophiles and nucleophiles, 28,29 and can be used to functionalize unprotected carbohydrates. 30 Baldwin et al demonstrated that lithiated trityl hydrazones act as 1,2diazaallyl anions and add to aldehydes. The resulting unstable azo-intermediate decomposes at room temperature in a carbon-centered radical that undergoes hydrogen atom transfer in the presence of a thiol (Figure 1A).…”
mentioning
confidence: 99%